1995
DOI: 10.1128/mcb.15.7.3823
|View full text |Cite
|
Sign up to set email alerts
|

MyoD-Induced Expression of p21 Inhibits Cyclin-Dependent Kinase Activity upon Myocyte Terminal Differentiation

Abstract: The terminal differentiation of C2C12 skeletal muscle cells involves the activation of unique sets of genes and an irreversible withdrawal from the cell cycle. This process is associated with a decrease in cdk2 activity in cell extracts. The decrease in cdk2 activity correlates with diminished levels of cdk2 and cyclin A and with a marked induction of the p21 cyclin-dependent kinase (cdk) inhibitor. The upregulation of p21 occurred at the levels of mRNA and protein, and p21 formed a complex with the cyclin kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
357
0
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(382 citation statements)
references
References 32 publications
23
357
0
2
Order By: Relevance
“…In examining the process of cell-cycle withdrawal accompanying differentiation, p21 levels have been shown to increase during NGF treatment of neuroblastoma (Poluha et al, 1996) and PC12 cells (Yan and Zi , 1995;van Grunsven et al, 1996a). This correlation is not limited to neural cells, as induction of p21 mRNA and protein has been detected during myogenic (Guo et al, 1995;Halevy et al, 1995), keratinocytic (Missero et al, 1995), promyelocytic (HL-60) (Jiang et al, 1994;Steinman et al, 1994), and human melanoma cell di erentiation (Jiang et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…In examining the process of cell-cycle withdrawal accompanying differentiation, p21 levels have been shown to increase during NGF treatment of neuroblastoma (Poluha et al, 1996) and PC12 cells (Yan and Zi , 1995;van Grunsven et al, 1996a). This correlation is not limited to neural cells, as induction of p21 mRNA and protein has been detected during myogenic (Guo et al, 1995;Halevy et al, 1995), keratinocytic (Missero et al, 1995), promyelocytic (HL-60) (Jiang et al, 1994;Steinman et al, 1994), and human melanoma cell di erentiation (Jiang et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Deletion of p21 was not able to substitute for p53 de®ciency in the rescue of the MDM2 null embryonic lethality, described above (Montes de Oca Luna et al, 1997). Moreover, although the p21 CIP1 gene is transcriptionally activated by p53 (el-Deiry et al, 1993), p21 CIP1 is also upregulated during myogenic di erentiation by a p53-independent mechanism thought to involve MyoDmediated transactivation (Parker et al, 1995;Guo et al, 1995;Halevy et al, 1995;Missero et al, 1995). It has also been shown that p21 CIP1 is poorly expressed in RMS cells lines, concomitant with both MyoD and p53 inactivity, and failure to G 1 arrest (Otten et al, 1997).…”
Section: Digging Deeper ± Prb and P53 At The Crossroadsmentioning
confidence: 99%
“…MyoD can promote cell cycle arrest by induction of the cyclin-dependent kinase inhibitor, p21 (Guo et al, 1995;Halevy et al, 1995), which along with other Cip1/Kip1 family members, p57 and p27, inhibits a wide range of cyclin-dependent kinases (CDKs) essential for cell cycle progression (Sherr and Roberts, 1999). It is generally accepted that induction of p21 follows myogenin expression during myoblast differentiation and that a high level of p21 is required for cells to maintain the postmitotic state.…”
Section: Introductionmentioning
confidence: 99%